2018
DOI: 10.1016/j.athoracsur.2018.02.076
|View full text |Cite
|
Sign up to set email alerts
|

Spread Through Air Spaces Is a Prognostic Factor in Sublobar Resection of Non-Small Cell Lung Cancer

Abstract: STAS is a prognostic factor of poor outcomes for sublobar resection in patients with lung cancer. The worse prognosis for sublobar resection would be associated with STAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 22 publications
8
56
1
Order By: Relevance
“…Importantly, surgical margin recurrence was identified in three patients (3.7%) who were all positive for STAS. This result is consistent with the findings of previous studies, and a surgical margin distance < 1 cm is reported to be a risk factor for local recurrence . In addition, Morimoto et al .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Importantly, surgical margin recurrence was identified in three patients (3.7%) who were all positive for STAS. This result is consistent with the findings of previous studies, and a surgical margin distance < 1 cm is reported to be a risk factor for local recurrence . In addition, Morimoto et al .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Shiono et al . reported that STAS is a prognostic factor in lung cancer patients undergoing sublobar resection, although this study included non‐adenocarcinoma and pathological stages I–III . In contrast, two further reports showed that STAS is a significant prognostic factor for postoperative survival in patients with pulmonary adenocarcinomas treated with lobectomy, but not wedge resection .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…STAS is also associated with recurrence and survival in squamous cell carcinoma, lung large cell neuroendocrine carcinoma, and lung small cell carcinoma, even lung pleomorphic carcinoma . STAS has been reported to be related with an aggressive tumor behavior, such as a larger tumor size, a high pathologic stage, lymphatic or vascular invasion, pleural invasion, tumor budding and increased micropapillary or solid structures in lung adenocarcinomas . We previously reported that the positive rate of STAS may be different for different invasive patterns and even lymph node metastasis .…”
Section: Discussionmentioning
confidence: 95%